Desenvolvimento embriológico em Dyckia polyclada L.B. Sm. (Pitcairnioideae - Bromeliaceae) - Martins, Merielem Saldanha (2016)
Bromeliaceae is one of the important neotropical families. It has approximately 3501 species. Pitcairnioideae has about 170 species. The present study aims to analyze and characterize the sporogenesis and gametogenesis in anthers and seminal rudiments of Dyckia polyclada L.B. Sm. (Pitcairnioideae-Bromeliaceae). Dyckia polyclada L.B.Sm. is native and endemic to Rio Grande do Sul and it is found in the central area of the state. The species presents perfect trimerous and heterochlamydous flowers. The androecium consists of six stamens, tetrasporangiate and dorsifixed anthers. Nine different phases of development were defined when it comes to the chemical constituents of the anthers. Only starch was detected in the connective. Starch and reserve lipids were observed in sporangia, microspores and pollen grains. The pollenkitt presents neutral lipids, essential oils and oleoresins in its chemical composition. The ovary in D. polyclada is superior, tricarpellate, trilocular and polispermic. Placentation is axial. The stigma is trífid of the conduplicate spiral. The ovules are anatropous, bitegmic and crassinucellate. The teguments are from dermic origin. The micropyle is formed by the inner tegument. The gametophyte is monosporic of the Polygonum type. The fibrillar aparattus is from pectic nature. Infralocular, labyrinthine and unstructured septal nectaries are present. The chalazal appendix is short and curved toward the raphe and features elongated cells with intracellular spaces. The obturator in D. polyclada has elongated dome-shaped cells and dense, vacuolated cytoplasm, coating the entire placental region. The presented data are unprecedented to the species and contribute to the understanding of the phylogenetic relationships within the family and for better understanding of the functioning of the reproductive process of Dyckia polyclada, given that, for lack of studies, the species is in the category of insufficient data and one cannot diagnose the degree of extinction.